2005
DOI: 10.1681/asn.2004080678
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Mobilization Therapy Accelerates Recovery of Renal Function Independent of Stem Cell Contribution

Abstract: Acute renal failure and tubular cell loss as a result of ischemia constitute major challenges in renal pathophysiology. Increasing evidence suggests important roles for bone marrow stem cells in the regeneration of renal tissue after injury. This study investigated whether the enhanced availability of hematopoietic stem cells, induced by stem cell factor and granulocyte colony-stimulating factor, to the injured kidney provides an adequate strategy for stem cell-based therapy to counteract renal ischemia/reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 41 publications
3
66
2
1
Order By: Relevance
“…But other studies have demonstrated that stem cells contribute to the regenerative process by producing protective and regenerative factors rather than directly using their differentiated progeny to replace damaged cells. [44][45][46][47] Our data indicate that cytokine-induced mobilization is effective in gentamicin-induced ATN, but our current study could not tell that the partial morphologic and functional improvements were due to multiple differentiation of bone marrow-derived cells or secretion of stimulatory or regenerative factors. Meanwhile, bone marrow contains various types of stem cells.…”
Section: Discussioncontrasting
confidence: 66%
“…But other studies have demonstrated that stem cells contribute to the regenerative process by producing protective and regenerative factors rather than directly using their differentiated progeny to replace damaged cells. [44][45][46][47] Our data indicate that cytokine-induced mobilization is effective in gentamicin-induced ATN, but our current study could not tell that the partial morphologic and functional improvements were due to multiple differentiation of bone marrow-derived cells or secretion of stimulatory or regenerative factors. Meanwhile, bone marrow contains various types of stem cells.…”
Section: Discussioncontrasting
confidence: 66%
“…Renal I/R injury was induced as described previously (58). Briefly, renal arteries were clamped for 45 minutes using microaneurysm clamps through a midline abdominal incision under general anesthesia (0.07 ml/10 g mouse of fentanyl citrate fluanisone midazolam mixture containing: 1.25 mg/ml midazolam [Roche Diagnostics Corp.], 0.08 mg/ml fentanyl citrate, and 2.5 mg/ml fluanisone [Janssen Pharmaceutica]).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of necrosis was scored by a pathologist in a blinded fashion on a 5-point scale: 0 = no damage, 1 = 10% necrosis of the corticomedullary junction, 2 = 10-25%, 3 = 25-50%, 4 = 50-75%, 5 = more than 75%. For immunostaining, 4-m tissue sections were incubated with specific antibodies for granulocytes (FITC-labeled anti-mouse Ly6G mAb; BD Biosciences-Pharmingen), apoptosis (rabbit anti-human active caspase-3; Cell Signaling Technology), GFP (rabbitanti GFP IgG; Molecular Probes), HMGB1 (rabbit-anti mouse HMGB1; Abcam), S100B (rabbit anti-S100B; Sigma-Aldrich) or CML ( N -epsilon carboxymethyl lysine) which has been identified as a major structure in advanced glycation end-products (AGE), mouse IgG, Biologo) followed by appropriate secondary antibodies as described before [15,16,[20][21][22][23]. To determine percentage of positive staining on kidney tissue slides, approximately 10 pictures of tissue section were taken under light microscopy (magnification !…”
Section: Plasma Biochemical Analysis Histology and Immunohistochemistrymentioning
confidence: 99%